THE RELATIONSHIP BETWEEN RESILIENCE AND THE LEVEL OF QUARTER LIFE CRISIS IN COLLEGE STUDENTS - Tri Muhana, Agung; Nastiti, Dwi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the correlation between students' levels of resilience and the severity of their quarter-life crisis. Method: Utilizing a quantitative correlational design, the research involved 160 students from STIKES Majapahit Mojokerto, selected through a saturation sampling technique. Data were collected using validated scales on resilience and quarter-life crisis, and analyzed using Pearson correlation. Results: The findings indicate a statistically significant negative correlation between resilience and quarter-life crisis (r = -0.260, p < 0.05), suggesting that higher levels of resilience are associated with lower levels of quarter-life crisis among students. Novelty: This study contributes to the limited body of research that addresses the protective role of resilience during early adulthood, particularly among students in Indonesia who are navigating the critical transition into the workforce and independent adulthood. While the quarter-life crisis is a well-known construct in developmental psychology, this research uniquely highlights resilience as a key mitigating factor in this specific cultural and developmental context.